Collective Action in Commons: Its Diverse Ends and Consequences - Autto, Hannu (fi=Turun yliopisto|en=University of Turku|, 2014)
Collective Action in Commons: Its Diverse Ends and Consequences explores new ways in which collective action theories can contribute to our understanding of natural resource management, especially the management of common-pools. Combining classical collective action theories and lessons from earlier empirical works, the study shows that cooperation among resource users is not only a possible solution to “the tragedy of the commons”, but it can be a part of the problem as well. That is, successful cooperation may increase the likelihood of resource depletion, for example, through more effective resource utilization or collusion against sanctioning and monitoring systems. The study also explores how analytic narratives can be used to tell the story behind problems of resource use and their solutions, including the diverse roles of cooperation.

Väitöskirjassa Collective Action in Commons: Its Diverse Ends and Consequences esitetään uusia tapoja soveltaa kollektiivisen toiminnan teoriaa luonnonvarojen, erityisesti yhteisvarantojen, hallintoa käsittelevässä tutkimuksessa. Yhdistämällä klassisia kollektiivisen toiminnan malleja ja aiempien empiiristen tutkimusten löydöksiä tutkimuksessa osoitetaan, että varannonkäyttäjien yhteistyö ei ole ainoastaan ratkaisu ”yhteisvarantojen tragediaan”, vaan se voi myös olla osa yhteisvaranto-ongelmaa. Onnistunut yhteistyö voi nostaa varannon ylikäytön todennäköisyyttä esimerkiksi, koska se mahdollistaa varannon tehokkaamman käytön tai varannonkäyttöä säätelevien valvonta- ja rankaisujärjestelmien kiertämisen. Tämä tutkimus myös osoittaa miten analyyttisia narratiiveja voidaan soveltaa ylikäyttöongelmien syiden ja ratkaisujen jäljittämiseksi, yhteistyön erinäiset roolit mukaan lukien.